2014
DOI: 10.1021/ci500091r
|View full text |Cite
|
Sign up to set email alerts
|

Does a More Precise Chemical Description of Protein–Ligand Complexes Lead to More Accurate Prediction of Binding Affinity?

Abstract: Predicting the binding affinities of large sets of diverse molecules against a range of macromolecular targets is an extremely challenging task. The scoring functions that attempt such computational prediction are essential for exploiting and analyzing the outputs of docking, which is in turn an important tool in problems such as structure-based drug design. Classical scoring functions assume a predetermined theory-inspired functional form for the relationship between the variables that describe an experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
178
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 176 publications
(185 citation statements)
references
References 61 publications
5
178
1
1
Order By: Relevance
“…Several cross-validation scenarios show that in any application RF-Score-VS comfortably outperforms classical SFs, even when using the most crude RF-Score v1 features1422.…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-validation scenarios show that in any application RF-Score-VS comfortably outperforms classical SFs, even when using the most crude RF-Score v1 features1422.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, machine‐learning SFs have exhibited a substantial improvement over classical SFs in different binding affinity prediction benchmarks . Furthermore, a number of studies have shown that a classical SF can easily be improved by substituting their linear regression model with nonparametric machine‐learning regression, either using RF or SVR .…”
Section: Generic Machine‐learning Sfs To Predict Binding Affinitymentioning
confidence: 99%
“…To this end, efforts have been conducted to make additional models for binding. Yet, this may not be necessarily the case as very specific descriptors and models do not show significant improvement on the prediction of binding affinity (Ballester, Schreyer & Blundell, 2014).…”
Section: Pose Vs Scoringmentioning
confidence: 99%
“…Their apparent underperformance can be attributed to the lack of implicit solvation and, in some cases, to the protonation state as it further deviates the RMSD when compared to crystal structures (Ballester, Schreyer & Blundell, 2014;Gürsoy & Smieško, 2017).…”
Section: Pose Vs Scoringmentioning
confidence: 99%